Gut bacterial communities in the freshwater snail Planorbella trivolvis and their modification by a non-herbivorous diet - Hu,Zongfu; Tong,Qing; Chang,Jie; Yu,Jianhua; Li,Shuguo; Niu,Huaxin; Ma,Deying (PeerJ, 2021)
The freshwater pulmonate snail Planorbella trivolvis is a common species in various bodies of water but is not native to China. Planorbella trivolvis usually live on diets with high fiber content, such as water grasses, algae and fallen leaves. These snails can attach to the wall of a water tank or to water grass and can be transported overseas to China through the ornamental fish trade. There are few studies investigating the intestinal microbiota of freshwater snails. In this study, using culture-independent molecular analysis, we assessed for the first time the complexity of bacterial communities in the intestines of reared snails. The intestinal microbiota in the snails fed different diets, that is, herbivorous feed (HV) with high cellulose and non-herbivorous feed (NHV) with low cellulose, were analyzed by Illumina sequencing. The results showed that the NHV-based diet significantly increased the body mass, shell diameter and specific growth rate of the snails after 60 days of rearing (P < 0.05). Histological experiments showed that the fat droplets in the epithelium columnar cells of the intestines of the NHV snails increased, and the cilia on these cells fell off. The sequencing results identified 486 and 195 OTUs in HV and NHV, respectively. Lots of bacteria were not reported previously in snails. The intestinal microbiota diversity index (Shannon, Simpson, Ace and Chao) in the NHV snails was significantly lower than that in the HV snails. The gut microbiota in the HV snails were predominantly Proteobacteria (52.97%) and Bacteroidetes (28.75%), while the gut microbiota in NHV snails were predominantly Proteobacteria (95.23%). At the genus level, Cloacibacterium (24.60%), Pseudomonas (4.47%), OM6ON (6.12%), and Rhodobacter (5.79%) were observed to be abundant in HV snails. However, Aeromonas (85.4%) was determined to be predominant in NHV snails. Functional prediction of the gut microbiome in snails by PICRUSt demonstrated a significant difference between the two groups, and the HV snails exhibited higher lignocellulose enzyme activity than did the NHV snails. This study represents a first step in characterizing the gut microbiota of the freshwater snail. Most of these microbes can process plant biomass and digest cellulose and lignocellulose, and the enzymes of these bacteria may have potential biotechnological applications in a variety of industrial processes.
Keywords: Planorbella trivolvis; Freshwater snails; Cellulose; Gut microbiota; Functional prediction; Intestine histology